Pengaruh Tren Pasar terhadap Pengambilan Keputusan Strategis Suatu Perusahaan - Idopati, Idopati; Royan, Muhammad Andi Alfin; Venesha, Reva; Noviyanti, Indah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2024)
This research is aimed at examining the influence of market trends on strategic decision making in an organization or company. Through a literature review method with in-depth qualitative data, the author conducted identification research related to various market trends that influence business strategy, including technology trends, Korea pop idol trends, economic trends, and others. Analysis of this data is carried out to understand how these trends influence decision making that can have a strategic impact, both directly and indirectly on the organization or company. The research results show that several organizations or companies that can anticipate and respond quickly to market trends can have a significant competitive advantage and can be one step ahead of their competitors. The practical implication of this research is the importance of continuous market monitoring and flexibility in formulating and adjusting business strategies. Research on market trends in decision making will contribute to the understanding of the relationship between market trends and strategic decision making, as well as provide guidance for business practitioners in facing a rapidly changing business environment.